UPAYA MASYARAKAT WAEREBO DALAM MEMPERTAHANKAN EKSISTENSI STRUKTUR LEMBAGA ADAT - Solo, Agustina; Tamim, Imron Hadi; Ranteallo, Ikma Citra (JURNAL ILMIAH SOSIOLOGI (SOROT), 2016)
ABSTRACT Â Waerebo village is a traditional village located in the village Satar Lenda, District Satar Mese West, Manggarai regency, East Nusa Tenggara Province. Waerebo villgae is the only one village in Manggarai are still keeping the legacy custom and culture in the world that is under development by globalization and modernization. One of the customs and cultural heritage that is still maintained by the community Waerebo is customary institutions. Until now, the traditional institutions in the Waerebo village still exist and still performing their duties and functions in society. In this paper will explain about the customs agency of Waerebo village were able to survive in the mids of globalization and modernization. Keyword: Waerebo, Authority, Headmen, Traditional Institutions